PENGARUH PROFITABILITAS, SOLVABILITAS, OPINI AUDITOR, UKURAN PERUSAHAAN, DAN REPUTASI AUDITOR TERHADAP AUDIT DELAY - Putri, Kiki Prasilya; Asyik, Nur Fadjrih (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to examine the influence of profitability, solvability, auditor opinion, firm size, and auditor reputation to the audit delay. The population is the companies which are listed in Indonesia Stock Exchange (IDX). The sample collection technique has been carried out by using purposive sampling and the determined criteria, therefore 72 the manufacturing companies which are consecutively listed during the years of 2010-2012 have been selected as samples. The hypothesis test has been done by using multiple regressions analysis technique. The result of the research shows that: (1) profitability does not have influence to the audit delay; (2) solvability has positive influence to the audit delay, it means that the company has responsibility to the external party, when the debt proportion is getting high, the audit delay is getting long and the company is unable to present its financial statement on time so it will reduce the trust of the external part; (3) auditor opinion does not have influence to the audit delay; (4) firm size does not have influence to the audit delay; and (5) auditor reputation has negative influence to the audit delay, it means that when the reputation of the Public Accountant Office is good, the completion process of audit statement is getting fast since the Public Accountant Office (KAP) will keep its image so it does not lose the trust of the client or public.Keywords: audit delay, financial performance, auditor opinion, auditor reputation.